Using Confidence Interval Based Estimation of Relevance (CIBER) to Determine Women's Emotion and Perception on Malaysia Road Environment During COVID-19 - Irza Hanie, Abu Samah; Ummi Naiemah, Saraih; Wan Ahmad Fauzi, Wan Husain; Nur Syafiqah, A. Rahim; Siti Aisyah, Panatik; Zulhaidi, Mohd Jawi (Social Science Research Network, 2022)
Road environment has been one of the factors contributing to road accidents. Research on the diversity of road users, condition and environment was discussed widely but in general. In Malaysia road environment is consider as one of the important factors in national agendas of Critical National Information Infrastructure (CNII). As women play a greater role in the population growth of a country, therefore, it is considered that women hold a great responsibility for nation sustainability. This paper focuses on road environment that centered on women's perception with the role of emotion as a predictor. This research also entails that emotions craft escapism which gives soothing sensation and relaxation on driving. Data collected via online google form and specifically targeted for female drivers. 93 respondents were able to participate in the survey. Results indicate that R2 equals to 0.27 from 99% confidence interval. The results predicted that emotions explained a moderate part in determining women's perception on-road environment. Meanwhile, respondents with negative emotions can separate their cognitive process, and does not affect their perception. The findings speculate that positive emotions have association towards perception, meaning that cognitive is relatively influenced by emotions, which in turn may affect on one’s judgment. This paper contributes to women's sentiments on the Malaysian road environment research using Confidence Interval Based Estimation of Relevance (CIBER). Current research highlights that CIBER technique is efficient in predicting the behavior and use for behavior modification in the future, and it is significant for policy revision and recommendation. This research contributes to the body of knowledge on escapism as means to perceive the road environment. limitation of this research is that it is focal to women and data collected during the pandemic may disparate from other events or situations. Finally, this research suggests that future behavior interventions among road users at the national level were appropriate to establish.